193 Evaluation of copper and selenium metabolism in Bos indicus and Bos taurus cows. (5th December 2019) - Ranches, Juliana; Picollo, Matheus; Silva, Gleise M; Vedovatto, Marcelo; Palmer, Elizabeth; Gouvêa, Vinicius N; Moreira, Aline; Miranda, Miguel; Aguiar, Caio; Moriel, Philipe; Vendramini, Joao; Arthington, John
Abstract: A two-year study was conducted to evaluate the differences in metabolism of Cu and Se among Bos indicus and Bos taurus cows. Thirty-two pregnant cows were enrolled in the study (n = 16/ year; 8 Brahman and 8 Black Angus). Cows were randomly assigned to individual pens at the beginning of the study, which was divided in 3 phases: depletion, repletion and calving. Throughout the study cows were fed grain supplement and had access to hay. During the depletion phase grain supplement was enriched with S (50g/head daily) to promote a decline in Cu and Se status. During the repletion phase, the extra S was removed from the grain supplement and Cu (100 mg/head daily) and Se were added (3 mg/head daily). To evaluate the mineral status, liver samples were collected from cows every 30 days and from calves at birth. Initial data was evaluated using the PROC MIXED procedure of SAS. No treatment effects (P = 0.14) were observed for liver Cu concentration, excepted for a day effect (P ≤ 0.01) as expected by the study design. Although there was a treatment x year interaction (P ≤ 0.01) for liver Se concentration a tendency for treatment (P = 0.10) was observed, where Angus cows tended to have greater liver Se concentration than Brahman cows (0.81 and 0.71 mg/kg; SEM = 0.048). No differences (P = 0.71) were observed for calf liver Cu (265 and 345 mg/kg; SEM = 94; respectively for Angus and Brahman) and Se (1.13 and 1.07 mg/kg; SEM = 0.11; respectively for Angus and Brahman) concentrations at birth. Similarly, no differences (P = 0.39) were observed for cotyledon Cu (7.7 and 6.0 mg/kg; SEM = 1.02; respectively for Angus and Brahman) and Se (0.74 and 0.77 mg/kg; SEM = 0.06; respectively for Angus and Brahman) concentrations.